TO SURVIVE OR TO FLOURISH? MINORITY RIGHTS AND SYRIAN CHRISTIAN COMMUNITY ASSERTIONS IN 20 TH CENTURY TRAVANCORE /KERALA - J. Devika and V. J. Varghese (Center for Development Studies, 2010)
The arrival of modernity not only constituted communities but also impelled them in competition against each other in Kerala. Modern politics of the state as a result is inextricably liked with intense community politics. The success of community politics for rights and resources varied across communities, so also strategies of assertion. This paper will focus on different instances of community assertions by the Syrian Christians in twentieth century Travancore/Kerala. The confrontation of the community with the Hindu state and the then Dewan in the 1930s, the ‘Liberation Struggle’ against the Communists during late 1950s and the anti-eviction movements of 1960s testifies to its lack of primordial adherences and openness to heterogeneous strategies as required by different historical circumstances. It moves freely from secular to non-secular, minoritarian to majoritarian and lawful to unlawful, with claims to a greater citizenship. The hegemonic developmentalist ideology to which the community subscribes, along with reiteration of a righteous and industrious citizenship, ensured the transformation of the ‘unlawful’ into ‘lawful’. Using even ‘state secularism’ in Travancore of the 1940s as a route of sectarianism, Syrian Christian politics resorted to no permanent self-representation, resulting in unfixed community constellations. The paper also suggests that the recent recourse of the community to minority rights may hint at an internal crisis and a loss of moral weight it possessed earlier.